GENDER DIFFERENCES IN THE RELATIONSHIP BETWEEN SELF-ESTEEM AND INTERNET ADDICTION : A STUDY AMONG UNIVERSITY STUDENTS - NURUL NAJWA, A RAMLI (Universiti Malaysia Sarawak (UNIMAS), 2020)
The aim of this study was to study gender differences in the relationship between selfesteem and internet addiction among university students. The relationship between gender towards self-esteem and internet addiction were also explained. The data was collected from 111 undergraduate final year students at a faculty in a university in Kota Samarahan. In this study, quantitative approach is applied to examine the relationship between variables. A cross-sectional study methodology was used to study the gender difference in the relationship between self-esteem and internet addiction and obtain the information from collecting the data through convenience sampling method. Statistical Package for Social Science (SPSS) was used to analyse the data. In this study, descriptive statistics is used to determine the demographic profile of students. Other than that, independent t-test is used to find the relationship between gender and internet addiction, and self-esteem. Pearson correlation is used to find the relationship between self-esteem and internet addiction. The gender shows there is no significant relationship between self-esteem and internet addiction. However, there is a significant relationship between self-esteem and internet addiction.